User Acceptance of a Digital Arabic Verb Recognition Tool: Validating TAM in Morphosyntactic Learning Contexts - Zuhriah, Zuhriah; Agussalim, Andi (Institut Agama Islam Negeri (IAIN) Kendari, 2026)
This study investigates user acceptance of Arabicapp based on morphosyntactic patterns. The application aims to support learners in recognizing verb forms and transitivity patterns, which are widely acknowledged as challenging aspects of Arabic grammar acquisition. To evaluate user acceptance, the study employed the Technology Acceptance Model (TAM), examining five core constructs: Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Use (ATU), Behavioural Intention (BI), and Actual Usage (AU). A quantitative survey was administered to a diverse group of participants, including university students, lecturers, and Arabic language practitioners. Data were collected through staged evaluations and analyzed using descriptive statistics, correlation analysis, and multiple regression techniques. The results indicate consistently high levels of acceptance across all TAM constructs, with ease of use and behavioural intention receiving the highest mean scores. However, regression analysis reveals that Perceived Usefulness significantly predicts Behavioural Intention, whereas Perceived Ease of Use does not show a statistically significant effect. This finding suggests that perceived instructional value plays a more decisive role than interface simplicity in determining adoption of morphosyntactic learning tools. Overall, the findings demonstrate that Arabicapp effectively supports Arabic grammar learning, particularly in verb identification tasks, and shows strong potential for use in both formal and non-formal instructional contexts. The study contributes to TAM-based research in language technology by highlighting that, in cognitively demanding learning environments such as morphosyntax, perceived usefulness emerges as the primary driver of user adoption.